Erratum: Kinetic and viscoelastic study of liquid thermoplastic matrix based on methyl methacrylate copolymers (Materials Research 26 (e20210619) DOI: 10.1590/1980-5373-MR-2021-0619) - Silveira, Daniel Consoli [UNESP]; da Silva Braga, Tiago Teixeira [UNESP]; dos Santos Conejo, Luiza [UNESP]; Ancelotti Junior, Antônio Carlos; Costa, Michelle Leali [UNESP]; Botelho, Edson Cocchieri [UNESP] (FapUNIFESP (SciELO), 2023)
In the legend of figures 2 and 3, where it was written: Figure 2. Heat flow vs. time curves for reactions with the autocatalytic mechanism of the polymeric systems. Figure 3. Dynamic DSC of MMA systems and BzO initiator in different concentrations. Should read: Figure 2. Heat flow vs. time curves (exo up) for reactions with the autocatalytic mechanism of the polymeric systems. Figure 3. Dynamic DSC of MMA systems and BzO initiator in different concentrations (exo up).